2t-11=23

Simple and best practice solution for 2t-11=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2t-11=23 equation:


Simplifying
2t + -11 = 23

Reorder the terms:
-11 + 2t = 23

Solving
-11 + 2t = 23

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 2t = 23 + 11

Combine like terms: -11 + 11 = 0
0 + 2t = 23 + 11
2t = 23 + 11

Combine like terms: 23 + 11 = 34
2t = 34

Divide each side by '2'.
t = 17

Simplifying
t = 17

See similar equations:

| 5n-5=11-n | | 6x+2(-6)=12 | | -7x-2x=18 | | 5=13 | | 5(2x+8)=-20+10 | | 5-2(4a+1)+3a= | | 6x+2(0)=12 | | (8+z)(2z-3)=0 | | 5(x+5)=5(x-5) | | 7x+9=71+x | | 5x-2=14x-38x | | -10x+4=-186 | | 5+49x=28x+17 | | (8a^5+6b)+-5a^5= | | 6(-4+x)=-42 | | 4+n=16 | | 2y-3=1.2-y | | 252=18n | | 5x+6x^2=5 | | (x+3i)(x+3i)= | | 5ln(x+3)=10 | | (x-y)dx+(x+y)dy=0 | | r/5=12/5 | | 9n+11=41-6n | | 4(x+2)-7=2x+2(2+x) | | 13=n/16 | | 38-18=4(x-2) | | -13=m+5 | | (-9a^7-4b)+-3a^7= | | 6x+11=2x+99 | | 2sinx-tanz=0 | | r/14=11 |

Equations solver categories